Earthquakes Impact, Community Vulnerability and Resilience - Santos-Reyes, Jaime (Earthquakes, 2019)
This book is a collection of scientific papers on earthquake preparedness, vulnerability, resilience, and risk assessment. Using case studies from various countries, chapters cover topics ranging from early warning systems and risk perception to long-term effects of earthquakes on vulnerable communities and the science of seismology, among others. This volume is a valuable resource for researchers, students, non-governmental organizations, and key decision-makers involved in earthquake disaster management systems at national, regional, and local levels.